Ex-ante economic assessment in incremental R&D projects: technical and development time uncertainties addressed by the real options theory - Leite,Luis Alberto Melchiades (2012)
This paper analyzes changes in the assessment of an incremental R&D project by an industrial firm with the progressive consideration of the endogenous treatment of its main sources of uncertainty: technical performance and development time. We found that the project, which was unfeasible under a deterministic assessment by Net Present Value (NPV) without flexibility, became feasible after the treatment of the technical uncertainty by a real options model (NPV with flexibility). Moreover, the project gained approximately 51 percent more value in flexibility when a treatment of the development time uncertainty was added to the model. In terms of additional flexibility per unit cost of the project, the gain is approximately 44 percent. This result demonstrates the importance of addressing the combination of these sources of uncertainty in R&D projects, especially those that are incremental, which is a difficult category to analyze in terms of quantitative benefits.